Phytochemical and Pharmacological Activities of Curcuma purpurascens Blume, A Review - Oktariani Pramiastuti; Subagus Wahyuono; Nanang Fakhrudin; Puji Astuti (Universitas Gadjah Mada, 2023)
Curcuma sp. is generally used for medicine, starch sources, preservatives, dyes and cosmetics. The use of Curcuma spp. for medical has increased because there have been many studies related to its active ingredients, such as flavonoids, essential oils, tannins, quinones, and terpenoids, as well as pharmacological activities, including wound healing, antioxidants, antifungal, anticancer, gastroprotective, and hepatoprotective. Curcuma purpurascens Blume is a species of Curcuma from family Zingiberaceae and used for traditional medicine. This article focuses on reviewing the literatures on C. purpurascens and discussing its morphology, phytochemical content, and pharmacological aspects. The method used to review this article was by exploring several databases such as Scopus, Pub Med, and Google Scholar to identify and download original articles and research journals related to the morphology, phytochemical content, and biological activity of Curcuma purpurascens Blume. The result of this review will later provide information about the uses and presence of Curcuma purpurascens Blume which is still rarely studied so further study related to its pharmacological activity tests and active compound as natural medicines can be explored.